Contenido de sodio en alimentos procesados comercializados en Colombia, según el etiquetado nutricional (2014)
ABSTRACT: Nutrition labels provide an opportunity to obtain data of sodium content in packaged foods. Objective: To describe sodium content, by nutritional labeling, from processed food obtained from a leader supermarket in Colombia. Materials and methods: Photos of food labels were obtained and divided into 15 categories. Sodium content per portion, 100 g, or 100 mL was analyzed. A descriptive analysis was performed by mean, range (maximum and minimum). Percentages of adequate intake and upper intake level that a portion would provide were determined. Results: 426 products were evaluated. Mean; range of sodium content per 100 g from categories with the highest mineral levels were: spices and essences (5829 mg; 0-21000), sauces and dressings (2426 mg; 0-7818), convenient meal (1929 mg; 41-6400), and processed meats (1068 mg; 44-7455). Variability in sodium content between categories and products from a same category was high. Conclusion: Data reported are an input to generate targets for sodium reduction in processed foods distributed in Colombia. Furthermore, they are an opportunity for research and development of food industry.